Studia Biblica;: essays in Biblical archæology and criticism, and kindred subjects (Clarendon Press, 1885)
1. Recent theories on the origin and nature of the Tetragrammaton, by S.R. Driver.- The light thrown by the Septuagint version on the books of Samuel, by F.H. Woods.- On the dialects spoken in Palestine in the time of Christ, by A. Neubauer.- On a new theory of the origin and composition of the synoptic Gospels proposed by G. Wetzel, by A. Edersheim.- A commentary on the Gospels attributed to Theophilus of Antioch, by W. Sanday.- The text of the Codex Rossanensis (SIGMA), by W. Sanday.- The Corbey St. James (ff), by J. Wordsworth.- A Syriac Biblical manuscript of the fifth century, by G.H. Gwilliam.- The date of S. Polycarp's martyrdom, by T. Randell.- On some newly-discovered Temanite and Nabataean inscriptions, by A. Neubauer.- Some further remarks on the Corbey St. James (ff), by W. Sanday.